Comparison of geneXpert versus sputum/gastric aspirate smearfor AFB for the diagnosis of pulmonary tuberculosis in children - Dr. Sandhya.V; Dr. Prabhavathi; M, Dr. Govindaraj (Pediatric Review: International Journal of Pediatric Research, 2018)
Introduction:This was a hospital based observational study for the comparison of geneXpert versus sputum /Gastric aspirate sample for AFB, for diagnosing pulmonary TB in children.The study was donein need for the useful diagnostic test, which is easy toperform, more sensitive and quicker. Gene Xpert assay is a single tube, cartridge based, real time PCR assay for the detection of tuberculosis. Materials and Methods: We enrolled 50 children for our study. Children attending inpatient or outpatient department were screened using aquestionnaire.Suspected children were investigated with Complete Blood count, ESR, Chest Xray andMantoux test. Sputum (in older children) was collected in a sterile container for AFB, and inspecialized container for geneXpert studies. In smaller children gastric aspirates were collected and sent for analysis and the results were compared. Results: Of the 50 children who were included in the study,42 (84%) were less than 10 years, 8 (16%) were 11-16 years. 46% of patients had positive contact history of tuberculosis. History of clinical tuberculosis was present in 58% of the patients. Gene X pert analysis came positive in 42% of the patients whereas sputum/gastric aspirate analysis for AFB came positive in 12% of the patients. In our study, sensitivity, specificity, positive predictive value and negative predictive value of Gene Xpert analysis came as 28.6%, 100%, 100% and 65.9% with 70% accuracy. Conclusion: Gene Xpert analysis can be effectively used as a quick and accurate diagnostic test for the diagnosis of pulmonary tuberculosis in children, especially in a low resource setting, although the bacteriological culture remains the gold standard.